2022
DOI: 10.1007/s12031-022-01965-4
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 and CD163 Ameliorate Microglia-Mediated Inflammatory Environment in the Aging Brain

Abstract: Aging declines cognitive functions, especially learning and memory. Microglia-mediated neuroin ammation occurs in age-related neurodegenerative diseases. Our study obtained the expression pro le of GSE11882 from the Gene Expression Omnibus database and used microarray data to explore the expression of age-related genes in the hippocampus. A total of 120 differentially expressed genes (DEGs) were screened out and subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. A prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This is confirmed by previous findings in other neuroinflammatory models (i.e., multiple sclerosis, Parkinson's disease, and sepsis) (Serrano-Martínez et al, 2024;Souza-Moreira et al, 2013;Wen et al, 2022), where cortistatin-modulated microglia markedly correlated with a better disease prognosis. Conversely, we observed a decreased expression of the scavenger receptor CD163, involved in the clearance of haemoglobin (Han et al, 2022). Interestingly, this factor is upregulated in patients with intracerebral haemorrhage and edema development (Roy-O'Reilly et al, 2017), suggesting a potential reduction of these events following cortistatin treatment.…”
Section: Discussionmentioning
confidence: 62%
“…This is confirmed by previous findings in other neuroinflammatory models (i.e., multiple sclerosis, Parkinson's disease, and sepsis) (Serrano-Martínez et al, 2024;Souza-Moreira et al, 2013;Wen et al, 2022), where cortistatin-modulated microglia markedly correlated with a better disease prognosis. Conversely, we observed a decreased expression of the scavenger receptor CD163, involved in the clearance of haemoglobin (Han et al, 2022). Interestingly, this factor is upregulated in patients with intracerebral haemorrhage and edema development (Roy-O'Reilly et al, 2017), suggesting a potential reduction of these events following cortistatin treatment.…”
Section: Discussionmentioning
confidence: 62%
“…As an emerging interdisciplinary subject, bioinformatics has been widely used in the field of life sciences. Recently, 10 Disease Markers the use of bioinformatics tools to study the genetic relationship between aging and inflammatory diseases, studies have found some correlation in molecular pathogenesis and disease development [46][47][48]. In this study, the four datasets identified 84 common DEGs, including 24 common upregulated genes and 5 common downregulated genes.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have highlighted CD45, CD68, and CD163 expressing cells as being frequently expressed in the pGBM TME (26,40). These markers are commonly expressed by TAMs and microglia (43,44). TAMs have been observed as a predominant cell population within the TME of pGBM (26,40).…”
Section: Characterization and Polarization Of Tumor-associated Macrop...mentioning
confidence: 96%